Expression of hormonal receptor in patients with metastasizing pleomorphic adenoma of the major salivary gland; a clinicopathological report of three cases - Noppadol Larbcharoensub (2018)
Background: Metastasizing pleomorphic adenoma is an uncommon malignant tumor of the salivary gland demonstrating benign epithelial and modified myoepithelial elements intermingling with tissue of mucoid, myxoid, or chondroid appearance that inexplicably manifests local or distant metastasis. Objective: To determine the expression of hormonal receptor in the patients with metastasizing pleomorphic adenoma of the major salivary gland. Material and Method: Medical records, clinical and pathologic findings of three patients who were diagnosed as metastasizing pleomorphic adenoma were reviewed. The immunohistochemical stains for estrogen receptor, progesterone receptor, and Ki-67 were performed. Results: Three cases of metastasizing pleomorphic adenoma, clinically presenting as painless, gradually enlarged cervical lymph nodes were reported. The pathologic examinations of the cervical lymph nodes are morphologically and immunohistologically identical to the sialoadenectomy specimen. Immunohistochemical stains show positive reactivity to progesterone receptor, but negative reactivity to estrogen receptor in both mesenchymal and epithelial components of pleomorphic adenoma. Conclusion: These are the first reported cases of metastasizing pleomorphic adenoma of the major salivary glands associated with expression of progesterone receptor in both specimens of sialoadenectomy and lymph node biopsy. This finding supports the pathogenesis of benign metastasis of tumor. However, the role of hormonal receptor in the pathogenesis and treatment of salivary metastasizing pleomorphic adenoma should be further investigated.